Characterization of Sodic Soils and Suggestions for Management of Chambal Command Area of Madhya Pradesh - and S.K. Dubey, Y.P. Singh, N. Gupta, Shashi Yadav, R.S. Tomar, N.P.S. Yadubanshi (Journal of the Indian Society of Soil Science, 2016)
Five representing pedons of sodic soils viz., Samai, Kirawali, Butrawali, Kutrawali and Saipura of Chambal command area of Madhya Pradesh state of India were selected for morphological characterization, status of exchangeable anions, cations, physicochemical properties and suggestions for sustainable management. Soils vary in colour from yellowish brown, dark brown to dark grey brown. The soil texture of pedons varies from sandy loam, sandy clay loam, clay loam to clay. The structure ranges from fine to moderate, angular to sub-angular blocky. Loose to very hard consistency of dry surface horizons was observed. Under moist condition consistency of soil was firm to very firm, whereas under wet conditions, the consistency was slightly sticky to very sticky of all pedons. The density of rooting zone was decreased with increasing contents of CaCO3. The ranges of ECe, pHs, and exchangeable sodium percentage (ESP) varied from 0.82 to 2.72 dS m-1, 7.7 to 9.5 and 17.81 to 37.24 of different horizons, respectively. Organic carbon (OC) ranged from 1.08 to 4.56 g kg-1 in different horizons and decreasing trend was noticed with depth in all pedons. An increasing trend in calcium carbonate content was noticed with depth in all pedons. The range of CaCO3 in upper horizon was from 0.5 to 1.2%, whereas in lower horizon from 2.5 to 6.5% and an increasing trend was noticed with depth in all pedons. Cation exchange capacities (CEC) ranged from 13.56 to 34.45 cmol(p+)kg-1. In general, the CEC decreased with increasing soil depth. The range of bulk density of different surface soil horizons was 1.46 to 1.53 Mg m-3. The bulk density was slightly increased in lower horizons in compared with upper horizons in all pedons. The dominating cations on the exchangeable complexes were Na+ followed by Ca2+ and Mg2+, whereas exchangeable anions were HCO3- followed by SO42-, Cl- and CO32-. Comparatively narrower Ca2+/Mg2+ ratio was registered in comparison with Na+/K+. The available N, P, K and S (kg ha-1) in upper horizons were 143 to 220, 8.6 to 18.8, 165 to 306 and 11.8 to 23.4 and in lower horizons 92 to 145, 6.0 to 9.5, 120 to 251 and 6.9 to 18.0, respectively. Similarly, ranges of Zn, Fe, Cu, Mn in mg kg-1 in upper horizons 0.26 to 0.62, 3.04 to 5.65, 0.28 to 0.45 and 1.32 to 2.21 and in lower horizon from 0.32 to 0.51, 2.84 to 3.79, 0.2 to 0.35 and 1.65 to 2.69, respectively. Available N, P, K and S were deficient, low to medium, medium to high and low to medium in all depths of horizons, respectively. As per characteristics all pedons were grouped as sodic soil. Leveling, bunding, deep tillage, use of gypsum or pyrite as per soil requirement, green manuring through sesbania recommended for all pedons, whereas pearlmillet, sorghum and cotton in kharif and barley, wheat and mustard in rabi season suggestions for pedon 1, 3, 4 and sesbania, cotton and sorghum in kharif and barley, wheat in rabi season for pedon 2 and rice, cotton, pigeonpea, and sorghum in kharif and barley, wheat and mustard in rabi season for pedon 5. Safer use of ground water after knowing hazardous effect through proper quality test for crop production is recommending. Similar, application of nutrients for crops for sustainable production system is recommended as per soil test for all pedons.